The Contribution of Organizational Culture and Leadership to Improving Work Behavior in Nagari IX Koto Sungai Lasi - Yeni, Afni; Nasrah, Rasidah; Adilfa, Fery (Universitas Negeri Jakarta, 2024)
Background By knowing the influence of organizational culture and leadership style, the nagari government can take strategic steps in managing these two factors to create a conducive work environment and encourage positive work behavior from nagari officials. Purpose The purpose of this research is to determine the contribution of organizational culture and leadership to improving work behavior in the Nagari IX Koto Sungai Lasi apparatus. Design/method/approach The research method used was survey with total population was 40 respondents, the data collection method used a questionnaire. Results The results of the coefficient of determination obtained a value of 0.329, that the contribution between the variables Organizational Culture and Leadership Style was 0.329 or 32.9% and influenced by other variables was 67.1%. The t-calculated result of Organizational Culture 0.753 > 2.024 has an influence and is not significant on the Work Behavior. The t-calculated results of Leadership Style < 3.699 < 2.024 have an influence and significance on the Work Behavior and the results of the f test are 9.072 > ftable 3.24 with a significance level of 0.001 < 0.05. The large fcount value of the ftable value and the significant value is smaller than 0.05 indicates that Organizational Culture and Leadership Style simultaneously or together have a significant and significant influence on the Work Behavior. Contribution/value This study concludes that organizational culture dan leadership is a key factor in the successful of work behavior.